Spontaneous resolution of haematuria and clot retention after covid-19: a case report - William Saputra Wijaya; Fauriski Febrian Prapiska; Yacobda Hamonangan Sigumonrong; Kharisma Prasetya Adhyatma (Medistra Medical Journal (MMJ), 2024)
COVID-19 has been associated with a hypercoagulable state which leads to an increase risk of thromboembolic events in blood vessels. The nature of renal manifestation of COVID-19 usually involves microvascular thrombosis resulting kidney injury. Major renal artery thrombosis in COVID-19 is considered quite rare. We present a case of a patient with recurrent haematuria and clot retention post PCNL for nephrolithiasis with an spontaneous resolution of complaints after infection with COVID-19. The patient was found to have a high D-dimer, fibrinogen values, and an elevated partial thromboplastin time. We reviewed existing literature to assess whether or not these events are related to one another